2013
DOI: 10.1186/1471-2164-14-350
|View full text |Cite
|
Sign up to set email alerts
|

RNA-seq analysis of single bovine blastocysts

Abstract: BackgroundUse of RNA-Seq presents unique benefits in terms of gene expression analysis because of its wide dynamic range and ability to identify functional sequence variants. This technology provides the opportunity to assay the developing embryo, but the paucity of biological material available from individual embryos has made this a challenging prospect.ResultsWe report here the first application of RNA-Seq for the analysis of individual blastocyst gene expression, SNP detection, and characterization of alle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
52
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(57 citation statements)
references
References 52 publications
5
52
0
Order By: Relevance
“…In general, the obtained results correspond to those commonly reported in other species (Iqbal et al 2014). However, it is noteworthy that the authors confirmed the possibility of identifying the sex of an embryo by comparing the levels of XIST (X inactive specific transcript, non-coding protein) previously reported in bovine embryos (Chitwood et al 2013). Furthermore, the transcriptome data have been analyzed according to pathways that may be involved in the creation of equine capsule.…”
Section: Gene Expression Profiling and Annotation Of Novel Genes In Tsupporting
confidence: 86%
“…In general, the obtained results correspond to those commonly reported in other species (Iqbal et al 2014). However, it is noteworthy that the authors confirmed the possibility of identifying the sex of an embryo by comparing the levels of XIST (X inactive specific transcript, non-coding protein) previously reported in bovine embryos (Chitwood et al 2013). Furthermore, the transcriptome data have been analyzed according to pathways that may be involved in the creation of equine capsule.…”
Section: Gene Expression Profiling and Annotation Of Novel Genes In Tsupporting
confidence: 86%
“…A limitation of the present study was that whereas the IVF blastocysts used for RNA‐seq were of both male and female sex, the SCNT blastocysts were male. It is possible that this could have influenced the expression level of some transcripts since the sex of the embryo affects the level of several actively expressed genes (Bermejo‐Alvarez, Rizos, Rath, Lonergan & Gutierrez‐Adan, ; Chitwood et al, ; Min et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…30,31 Briefly, 3-4 groups of 10 in vitro matured oocytes and in vitro produced embryos were used per stage of development. In a group of embryos, α-amanitin was added at the zygote stage at 50 μg/ ml and 8-cell embryos collected 56 h post fertilization.…”
Section: Rna-seq Datamentioning
confidence: 99%